Evolving understanding of antibody-dependent enhancement (ADE) of SARS-CoV-2 - Yang, Yalong; Xu, Fenghua (Frontiers in Immunology, 2022)
Since immune system and internal environment in vivo are large and complex, the interpretation of the observed immune effect from the perspective of a single immune cell or antibody seems a little feeble. Many studies have shown that specific antibodies against " former" viruses have a reduced ability to neutralize “new” mutant strains. However, there is no comprehensive and clear view of whether there will be Antibody-dependent enhancement (ADE). We review the latest relevant studies, hoping to explain the ADE of SARS-CoV-2 infection sometimes observed in some patients.